Strategi Pengembangan Kawasan Geopark di Pulau Belitung Sebagai Destinasi Wisata Berdaya Saing Global - Farah Zafira (Departemen Ilmu Pemerintahan Fisip Unhas, 2022)
Belitung Island is one of the islands in Indonesia with abundant natural resources. Because of its wealth ranging from geological, biological to local culture, right in 2021 UNESCO designated the Belitung Geopark as the world's geopark area with a total of seventeen destinations that can attract tourists from abroad and within the country. The establishment of the Belitung Geopark by UNESCO cannot be separated from the hard work of the management and support from the local community and government. A professional and reliable strategy was designed by the manager to develop the geopark area on Belitung Island. The existence of this study aims to analyze the strategies used by the geopark manager in developing the Belitung Geopark area so that it can be included in the UNESCO Global Geopark list. This article uses qualitative research methods with primary and secondary data collection techniques. The primary data source was conducted by interviewing the Chairman of the Belitung Geopark Management Agency. Secondary data is obtained through literature study from journals, articles, and various other written sources.